Effect of vacuum cooling and packaging on physico-chemical properties of 'Red' holy basil - D. Boonyakiat (2018)
The effect of vacuum cooling and type of packaging on the physico-chemical properties of 'Red' holy basil stored at 13°C, the most proper temperatures to store holy basil from the study, was investigated. The results showed that vacuum cooling had no effect on the loss of fresh weight, the change of color, the amounts of vitamin C and chlorophyll in 'Red' holy basil, but was an important factor in maintaining longer shelf life than those of holy basil not vacuum-cooled. The amounts of phenolic content and antioxidant activity in holy basil after vacuum cooling were significantly higher than those found in holy basil without vacuum cooling. Type of packaging had a significant effect on fresh weight loss, phenolic compounds and antioxidant but had no effect on the amounts of color change, vitamin C and chlorophyll. Holy basil packed in PVC film wrapped foam trays suffered a smaller loss of fresh weight and at the same time measured lower amounts of phenolic compounds and lower antioxidant activity than those packed in holed plastic boxes. There was no interaction effect between vacuum cooling and type of packaging on the loss of fresh weight, the change of color, the amounts of vitamin C and chlorophyll in holy basil but it significantly affected total phenolic content, antioxidant activity and shelf life. The research also exemplified that 'Red' holy basil precooled and stored under those optimal conditions is significantly better preserved with longer shelf life of about 9 days as opposed to the normal length of 4 days.